Analisis Pola Produktivitas Pengarang Pada Jurnal “Visi Pustaka” Tahun 2016-2021 Dengan Menggunakan Hukum Lotka (Analysis of Author Productivity Patterns in the "Visi Pustaka" Journal 2016-2021 Using Lotka's Law) - Yunus Winoto; Yuliani Yuliani (Pustabiblia: Journal of Library and Information Science, 2022)
Author productivity is one of the studies in the field of bibliometrics that needs to be studied. By knowing the productivity of the author, it will be seen who produced the most works in a certain period of time. The purpose of this study was to analyze the author's productivity patterns in the Visi Pustaka Journal for the 2016-2021 time period. The method used is descriptive quantitative. Data collection techniques were carried out by means of documentation and literature studies. The existing data is then processed using Lotka's Law. The productivity measurement technique is done by straight count, which is the calculation of the main author only. The results showed that the authors who contributed 1 article to the Visi Pustaka Journal in 2016-2021 were 75% of the total authors. The most productive authors are Abdul Rohman Saleh and Andi Saputra who produced 5 articles during the 2016-2021 period. Then, based on the Kolmogorov-Smirnov test, the results show that the Dmax value is greater than the critical value. This means that there is a significant difference between the frequency distribution of author productivity based on observations and the theoretical productivity frequency distribution of Lotka's Law.